Older Adults' Perceptions of Age-friendliness in Hong Kong. (30th May 2018) - Chui, Cheryl Hiu-Kwan; Tang, Jennifer Yee Man; Kwan, Christine Manlai; Fung Chan, On; Tse, Michael; Chiu, Rebecca Lai Har; Lou, Vivian Wei Qun; Chau, Pui Hing; Leung, Angela Yee Man; Lum, Terry Yat Sang
Abstract: Background and Objectives: There is little understanding about how rapid urban development has affected the extent to which communities are able to optimize health and participation opportunities for older adults in Hong Kong. Our objective was to examine what older residents perceive to be the shortcomings of their communities in meeting their psychosocial and physical needs as they age. Research Design and Methods: In reference to the WHO Age-Friendly Cities Project Methodology: Vancouver Protocol, we conducted nine focus groups comprising 65 participants for an Age-Friendly City baseline assessment in two districts in Hong Kong, China. Participants were asked to share their views on their respective district of residence, and identify aspects of the city they found unfriendly. Data generated from interviews were analyzed using thematic analysis. Results: Five of the following key themes were identified: the failure of public transportation to cater to the needs of older adults; a lack of public space for recreation and socializing; diminishing human interactions in welfare services; physical and financial challenges relating to housing; and workplace discrimination against older adults. Discussion and Implications: These findings underscore the importance of prioritizing the social welfare of older adults in building a more inclusive and age-friendly city. They also highlight the difficulties in fostering an inclusive environment while ensuring efficiency and profit maximization.